PENGARUH KUALITAS PELAYANAN ISLAMI TERHADAP KEPUTUSAN NASABAH DALAM PEMBIAYAAN MURABAHAH - Mulyani Rizki (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2021)
Service quality in the Islamic concept can be said that the overall features and characteristics of a product or service that depend on its ability to satisfy stated or implied needs and in accordance with Islamic values.21 In this concept Islam teaches that providing services in the form of goods or services. must be of quality in accordance with Islamic values, and do not give bad and not quality because it will only harm both parties. Service quality in Islam is defined as a customer's assessment of the superiority or privilege of a product or service as a whole which is of course based on Islamic principles, the quality of service in Islam provides services that basically every activity related must be based on compliance with sharia which is full of values. -moral and ethical values. Improving the quality of service in Islam is very necessary in order to determine customer decision making. However, it will not run well if it is not accompanied by quality decision making. To maintain the quality of service in Islam is not only the duty of the employees, but all the members involved. Judging from the above phenomena, the quality of Islamic services can be taken into consideration for customer decision making. The purpose of this study was to determine how the influence of Islamic service quality on customer decisions in murabahah financing. The number of samples in this study was 100 respondents, this study used a quantitative approach. The data collection technique in this study used a questionnaire, and the sampling technique used the incidental sampling method using the hair formula. The data obtained were then processed with SEM AMOS Version 20. The results of this study indicate that the CR value is 3,418 > 1.96 and the probability is 0.000 < 0.05, so it can be concluded that Islamic Service Quality has a positive and significant effect on Customer Decision Making in Murabahah Financing.